Evaluation of efficacy of NIBRG-14 vaccine against highly pathogenic H5N1 viruses isolated during 2011 influenza outbreaks in Vietnam - Huy Tung, Dau; Van Quyen, Dong; Tung, Nguyen; Xuan Hanh, Tran; Young Bong, Kim; Duy Khang, Dinh (Vietnam Journal of Science and Technology, 2017)
Highly pathogenic avian  influenza (HPAI) H5N1 viruses continue to be endemic  in many Asian countries causing  lethal  infections  in human. The vaccine virus  (NIBRG-14) developed from a H5N1 virus strain (A/Vietnam/1194/2004) has been approved by WHO for use in human as  well  as  poultry  vaccine.  It  is  well-known  that  the  A/H5N1  viruses  have  diversified  both genetically  and  antigenically  allowing  them  to  escape  from  the  host  immune  surveillance system.  Therefore,  evaluation  of  the  vaccine  immunogenicity  and  its  relationship  to  newly emerging  viruses  is  crucially  important. NIBRG-14 virus particles propagated  in  embryonated chicken eggs were inactivated with formalin and adjuvanted with mineral oil to form a water-in-oil emulsion. The  resulting vaccine was  injected  subcutaneously  into chickens and ducks. The vaccinated birds were challenged with  the HPAI virus strains circulating  in Vietnam  including clade  1,  clade  2.3.2.1a  and  2.3.2.1b  at  day  21  post-vaccination  (p.  v.).  We  observed  that vaccinated birds were protected from manifestation of disease signs upon challenge with HPAI clade 1 and clade 2.3.2.1a viruses; however,  it did not confer protection against clade 2.3.2.1b challenge  andstressing  the  need  for  development  of  new  effective  vaccines  against  the  newly emerging viruses.